ANALYSIS OF FACTORS AFFECTING SUPPLY CHAIN PERFORMANCE IN SME TEMPE CHIPS IN SANAN VILLAGE MALANG - Nugroho, Aditya; Surachman, Surachman; Rofiq, Ainur (Jurnal Aplikasi Manajemen, 2018)
Small Medium Enterprise (SME) that has good supply chain performance can help its ability to solve business problems. In fact, there are still a lot of SMEs that fail in supply chain management due to many factors influencing their implementation. This research aims to analysis relation between factors influencing supply chain and the performance of supply chain management in Tempe Chips Industries in Sanan Village Malang.Data collections were done through questionnaire deployed to 200 owners or manager of Tempe Chips SME in SananVillage, Malang. Data were analyzed using Structural Equation Modeling (SEM). Analysis result shows that information sharing and customer service give the most dominant influence to supply chain management’s performance in Sanan’s Tempe Chips industries.